The Impact of Social-Emotional Learning on Academic Achievement in Elementary Schools - Yulis Mardotilla; Roro Dita Hapsari; Azka Nahya Amanta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study evaluates the relationship between social-emotional learning (SEL) programs and academic performance in elementary school students. Using a quasi-experimental design, we compare the academic outcomes of students who participated in SEL programs with those who did not, focusing on math and reading scores. Data analysis reveals that students involved in SEL programs showed a significant increase in both academic performance and emotional regulation skills. The results emphasize the importance of SEL in fostering not only emotional well-being but also academic success.